Keabsahan Hibah Wasiat yang Dibuat di Hadapan Notaris kepada Ahli Waris Menurut Undang-Undang - Marvel Romi Sutiono; Dyah Ayu Prameswari Setyowati; Fahrel Faadhilah Wiramansyah; Alfian Anugrah Saputra; Venatha Tanoto (UNES Law Review, 2023)
Chinese inheritance is regulated in Book II of the Civil Code on property, adhering to a closed system, meaning that no new articles or regulations are allowed other than existing ones. Inheritance assets left by the testator by law are transferred to the heirs without distinguishing between the gender of the heirs according to the law or by appointment as a will. Even though the first class of heirs can have their rights violated, only by law. Deviations are based on customary law as something that is contrary to the matters stipulated in Article 18B paragraph (2) of the 1945 Constitution. Wills can be given to anyone, including heirs, but are not allowed to harm the heirs' absolute rights according to the law. The provisions of Article 914 of the Indonesian Civil Code, if you leave four children as heirs, the full share of the heirs is three-quarters, if given as a whole, in contrast to the absolute right share known as the share that must be given to the heirs.